Critical Thinking Ability Based on Student Gender in Biology Learning at SMA Negeri 4 Pekanbaru - Ferazona, Sepita; Anggraini, Teti Dwima; Suryanti, Suryanti; Hajar, Ibnu (Universitas Lampung, 2023)
One of the goals of 21st Century education is to develop students' thinking skills, one of which is critical thinking skills. The diversity of student problems in schools is one of the topics of discussion and research in the world of education. One of the main learning processes is student differences, especially gender differences. The influence of gender or gender differences on various student abilities has been revealed in previous research. This research was conducted at SMA Negeri 4 Pekanbaru. The population in this study were students of class XI MIPA. The research method used is descriptive method, which is a research method used to describe problems that occur at the present time or are ongoing, aiming to describe what happened as it should have been when the research was conducted. According to the graphic data above, the highest score interpretation is found in female students, namely the range of values 79-65 in the moderate category and the number of female students who get this range of values is 10 out of 19 people. Meanwhile, only 8 out of 17 male students obtained a score range of 65-79. Based on the results of the research that has been carried out and the discussion that has been presented, it can be concluded that there are gender differences, female students get a percentage of 26.7% with 3 indicators of critical thinking skills while male students get a percentage of 14.5% with 2 indicators of critical thinking skills. So the percentage of female students has a higher critical thinking ability than male students.Keywords: critical thinking ability, gender, learners